IDENTIFYING PRIORITIES FOR IMPROVED CHILD HEALTHCARE: A MIXED METHODS ANALYSIS OF SAFETY INCIDENT REPORTS. Issue 11 (22nd October 2015) - Rees, Philippa; Edwards, Adrian; Powell, Colin; Williams, Huw; Hibbert, Peter; Makeham, Meredith; Luff, Donna; Parry, Gareth; Sheikh, Aziz; Donaldson, Liam; Carson-Stevens, Andrew
Abstract : Background: Globally children are failed on numerous indicators of care quality, most of which is provided in the primary care setting. There is a paucity of research and development to explain iatrogenic harm in the primary care setting, not least safety events involving children. Objectives: We identified priority issues (by frequency and level of harm) reported by clinicians from the England and Wales National Reporting and Learning System (NRLS). The concepts and content within reports empirically informed a systems-level Driver diagram for improvement of child health. Methods: We undertook a retrospective cross-sectional mixed methods study of safety incident reports from primary care involving 'unwell' children between 2003–2013. We classified incident types, contributory factors, and harm outcomes. Data underwent exploratory analysis to explore the relationship between variables, and thematic analysis provided in-depth contextual insights. Subject matter experts identified key drivers for improvement. Results: Of 2191 incidents identified, priority improvement areas included: medication provision in the community pharmacy setting; diagnosis, assessment, and timely referral of acutely unwell children in out of hours care settings; and communication with and about the child. Reported causes are outlined in the attached Ishikawa diagrams (figures 1–3) and the related Driver diagram (figure 4) summarises opportunities to mitigate priority concepts. Conclusions: Analysis of incident reports can be used to inform national-level improvement initiatives when there is a paucity of existing available evidence. Further validation and development of the proposed designs are needed with the clinical teams responsible for care delivery.Figure 1 Figure 2 Figure 3 Figure 4